EP235/#216 Comparison of the comprehensive complication index and clavien-dindo classification in predicting post-operative outcomes following cytoreductive surgery in ovarian cancer. (4th December 2022) - Kengsakul, Malika; Boer, Gatske Nieuwenhuyzen-De; Udomkarnjananun, Suwasin; Kerr, Stephen; Doorn, Helena Van; Beekhuizen, Heleen Van
Abstract : Objectives: The comprehensive complication index (CCI) is an instrument for reporting the cumulative post-operative complications while Clavien-Dindo classification (CDC) reports the most serious event. This study aims to validate the CCI for advanced stage epithelial ovarian cancer (AEOC) after cytoreductive surgery and compare its diagnostic performance with CDC. Methods: Complications after cytoreductive surgery for primary AEOC were classified using CDC and CCI. Logistic regression was used to determine the association between CDC and CCI with prolonged length of hospital stays (PLOS), intensive care unit (ICU) admission, readmission and time to chemotherapy (TTC). Area under the receiver operating characteristic (AUC) was used to establish the diagnostic performance of each classification. Results: Totally, 300 patients were included from February 2018 to September 2020. Thirty days post-operative complications occurred in 146 patients of whom 30% had multiple complications (range 2–6 events). Severe complications were diagnosed in 17% of patients when using the CDC while the percentage increased to 30% when using the CCI. In regression analysis, both CDC and CCI presented as predictors for PLOS (>9 days), TTC >42 days, ICU admission and readmission (all p <0.05). AUC demonstrated that CCI (0.843, 95% CI 0.79–0.90) performed better than CDC (0.813, 95% CI 0.75–0.88) for PLOS. Both systems equally showed a fair diagnostic performance for TTC >42 days (both AUC 0.630, 95%CI 0.55–0.71). Conclusions: The cumulative score of CCI had shown a superior diagnostic performance for PLOS than CDC in AEOC. The use of the CCI should be considered in other gynecological evaluations.